If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.3 + 5x = 3x + -5.7 Reorder the terms: 2.3 + 5x = -5.7 + 3x Solving 2.3 + 5x = -5.7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2.3 + 5x + -3x = -5.7 + 3x + -3x Combine like terms: 5x + -3x = 2x 2.3 + 2x = -5.7 + 3x + -3x Combine like terms: 3x + -3x = 0 2.3 + 2x = -5.7 + 0 2.3 + 2x = -5.7 Add '-2.3' to each side of the equation. 2.3 + -2.3 + 2x = -5.7 + -2.3 Combine like terms: 2.3 + -2.3 = 0.0 0.0 + 2x = -5.7 + -2.3 2x = -5.7 + -2.3 Combine like terms: -5.7 + -2.3 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 7(x-2)=3+3x | | 19=x-7 | | 14=3/2x-7 | | x/456=4 | | x/4456=4 | | 2x-14=2(2x+3) | | 9x-7=23x-14 | | x-2.6=7.3 | | 27=46+2x-1x | | 1.5m=0.5 | | -6x-21+9x=42 | | 2x+6=-7x-9 | | 27-(x+9)=4x-2 | | 6x-(2x+4)-(x+3)= | | 7(2y+1)=2(y-13) | | 0.4=0.75+y | | -6b+5(1-b)=-8b+26 | | (2x-1)(x^2-3x+5)=0 | | 3(2x+1)+1+2x=3(2x+2)+x | | 2X^2-16X+64= | | 7y-9-4y+4=0 | | 1.2x=40.8 | | 0(2x-4)^-11/2 | | -5+x-9=15 | | -1/4a7/4a=-21 | | 3/5x-3=2.25 | | 0.4=0.75y | | -(-5-6n)-3(2n+3)=3 | | 3x+4=-2x-14 | | -12-1x=8-3x | | 5x-3y=10fory | | -6=m+(-25) |